Immune markers for pulmonary aspergillosis in patients with chronic obstructive pulmonary disease: a narrative review - Hu, Yuke; Wang, Xingbo; Wu, Hao; Deng, Haibo; Gao, Fei; Wu, Yonghong (Frontiers in Immunology, 2025)
COPD complicated by pulmonary aspergillosis (COPD-PA) encompasses invasive, chronic, and allergic phenotypes and is increasingly recognized as a high-burden comorbidity. Clinical recognition is often hindered by nonspecific manifestations, corticosteroid-suppressed inflammatory signs, and the suboptimal performance of serum galactomannan in non-neutropenic hosts. To define the translational utility of immune biomarkers in this population, evidence was synthesized from international guidelines and contemporary studies in COPD-enriched cohorts, and performance was appraised across diagnostic, monitoring, and prognostic domains. Convergent findings indicate that bronchoalveolar-lavage galactomannan facilitates early diagnosis; serum galactomannan indices stratify risk during exacerbations; Aspergillus-specific IgG supports rule-in for invasive and chronic disease; and pentraxin-3 adds prognostic information. Cytokines central to COPD-PA pathobiology, including interleukin-1β, interleukin-6, interleukin-8, and interleukin-17, provide adjunctive diagnostic value, whereas (1→3)-β-D-glucan shows limited specificity. On this basis, a three-tier framework was developed that classifies biomarkers as clinically validated, mechanistically promising, or exploratory, and this framework was translated into subtype-tailored panels and decision rules that favor either-positive criteria for screening and both-positive criteria for confirmation. It is concluded that immune biomarkers complement microbiology and imaging, expand access when bronchoscopy or biopsy is not feasible, and enable longitudinal risk stratification. Priorities include COPD-specific thresholds, assay standardization, and multicenter validation, with particular emphasis on chronic pulmonary aspergillosis and allergic bronchopulmonary aspergillosis. Biomarker-guided immunomodulation may benefit selected phenotypes but requires rigorous evaluation before clinical adoption.